MORTALITY IN PARKINSON'S DISEASE AND ATYPICAL PARKINSONIAN DISORDERS. Issue 11 (14th October 2015) - Macleod, Angus; Counsell, Carl
Abstract : Background: We evaluated the mortality associated with Parkinson's disease (PD), Lewy body dementia (LBD), progressive supranuclear palsy (PSP), multiple system atrophy (MSA), and vascular parkinsonism (VP) using a community-based incident cohort. Methods: All incident parkinsonism cases identified over 4.5 years (2002-4, 2006-9) were tagged to the NHS central register for regular death notifications. Kaplan-Meier survival probabilities were plotted. Standardised mortality ratios (SMRs) and life expectancy, adjusted for age, sex and calendar year, were calculated using regional mortality data. Results: Until June 2014, 90 deaths occurred in 198 PD patients, and 107 deaths in 117 patients with other syndromes. Median survival in PD, LBD, PSP, MSA, and VP was 7.8 (6.7–9.4), 3.3 (2.3–4.1), 2.6 (1.1–3.8), 5.1 (1.3–NA), 2.1 (1.5–3.4) years, respectively. SMRs were 1.5 (1.2–1.9), 4.2 (3.0–5.9), 3.8 (2.6–5.5), 1.8 (0.9–3.4), 4.2 (3.0–6.0) respectively. In PD, median survival was lower than life expectancy, but more so in under 65s. Conclusions: Mortality in PD was increased by 50% over expected population mortality. Younger patients have proportionally more to lose. Survival was much poorer in other syndromes.